TiO2 Fabricated from Vietnamese Ilmenit Applying for Battery Anode - Thang, Doan Ha; Thuan, Vu Manh; Hang, Bui Thi (VNU Journal of Science: Mathematics - Physics, 2016)
Abstract:  In this study, TiO 2 was fabricated from Vietnamese ilmenite using plasma treatment. It was used as the active material in the metal-air battery to find the better anode material for metal-air battery. The physical and electrochemical properties of TiO 2 samples were investigated using X-ray diffraction (XRD), scanning electron microscopy (SEM) and cyclic voltammetry (CV). The obtained results showed that pure TiO 2 fine powder was successfully fabricated by plasma treatment and it can be used as the anode material in metal-air batteries. The influence of Acetylene Black (AB) additive on the electrochemical behaviors of TiO 2 /AB and TiO 2 /Fe 2 O 3 /AB electrodes were investigated. The prepared TiO 2 could be a promising candidate for a metal/air battery anode. Keywords: TiO 2 particles, plasma, carbon additive, TiO 2 -Fe 2 O 3 /AB composite electrode, Fe/air battery anode.